SUSTAINABLE LAST-MILE DELIVERY: OPTIMIZING PROJECT STRATEGIES FOR REDUCING CARBON FOOTPRINT IN URBAN LOGISTICS IN NIGERIA - Benita I. Abuo; Lorna M. Muthengi; Amos A. Fagbuyi; Babere D. Marwa (Utilitas Mathematica, 2025)
The study examined Sustainable Last-Mile Delivery: Optimizing Project Strategies for Reducing Carbon Footprint in Urban Logistics in Nigeria. The specific objectives are to; examine the effect of alternative transport modes on Reducing Carbon Footprint in Urban Logistics and evaluate the effect of adequate infrastructural development on Reducing Carbon Footprint in Urban Logistics in Nigeria. A descriptive research design was adopted for the study. A structured questionnaire design with a five-point Likert scale was used to collect data for the study. The data were analyzed, using statistical tools such as simple percentages, and Chi-square analysis was utilized to test the hypotheses. The result revealed that alternative transport modes have no significant effect on Reducing Carbon Footprint in Urban Logistics, with a p-value (0.104 >0.05). while adequate infrastructural development has a significant effect on Reducing Carbon Footprint in Urban Logistics, with a p-value of (0.000 < 0.05) in Nigeria. The study concluded that Well-planned infrastructure facilitates efficient last-mile delivery, reduces congestion, and minimizes fuel consumption, thereby contributing to environmental sustainability. The study recommended, among others, that Urban planners and logistics stakeholders in Nigeria prioritize adequate infrastructural development as a key strategy for reducing the carbon footprint in urban logistics.